ORGANIZATIONAL COMMITMENT IN ACHIEVING JOB SATISFACTION AND THE ESTABLISHMENT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): A SYSTEMATIC REVIEW OF THE LITERATURE - Diana Hayati; Meiske Claudia (Adisam Publisher, 2024)
This study focuses on investigating the link between organizational commitment (OC), job satisfaction (JS), and the emergence of employees' Organizational Citizenship Behavior (OCB). OCB involves employees voluntarily going above and beyond their formal duties. Various organizational factors influence the achievement of OCB, and high job satisfaction among employees plays a crucial role as a significant contributor. Various factors influence job satisfaction, and one such crucial variable is organizational commitment, which plays a pivotal role in establishing a positive work environment. Organizational commitment (OC) doesn't arise spontaneously; somewhat, it is shaped through a series of processes involving the entire human resources system and various supportive mechanisms. This commitment is intricately connected to preserving employees' mindsets and cultivating a sense of unity and loyalty towards the company. Emphasizing organizational commitment as a critical factor in a company's success, this concept is instrumental in enhancing employees' job satisfaction. As a result of this heightened satisfaction, employees are motivated to voluntarily exceed their formal obligations, contributing to the company's advancement. Essentially, organizational commitment is a catalyst, prompting employees to willingly contribute to their company's progress, illustrating the interconnectedness of commitment, job satisfaction, and OCB.